Efeitos de variáveis macroeconômicas no nível de liquidez de empresas brasileiras - Coelho, Lucia Borges (2012)
Due to markets evolution and the possibility to access infonnation on real time, the companies are very exposed to variation on their liquidity. lt arises a necessity of studying what affects its operation and how they are affected by shocks at the economy. This work has as objective to investigate how variations on macroeconomics variables, like for example, changes on exchange rale, at GDP (Gross Domestic Product), on inflation and on interest rales impact the liquidity levei o f companies. There were selected data of aclive Brazilian companies ofthe period of2003 until 20 li (qumterly data), with stocks negotiated at BM&FBovespa and that don't belong to financiai and insurance market. The results suggest that the company's liquidity levei is affected for some variation on macroeconomics variables. lt was verified that some variables as GDP, IBOVESPA and interest rates positively relates to current liquidity index. On the other hand, variables as exchange rate and inflation negatively relates to the liquidity index.